KREATIVITAS GURU AGAMA ISLAM DALAM MENINGKATKAN KUALITAS PENDIDIKAN AGAMA ISLAM DI SMP IT ISHLAHUL UMMAH PRABUMULIH - RULITAWATI RULITAWATI; YUNIAR HANDAYANI; DARUL ARQOM; RUSKAM SUAIDI (Raudhah - Proud To Be Professional, 2023)
The creativity of religious teachers is the teacher's ability to find thoughts about new ideas in solving problems related to science, especially knowledge about Islamic religious education. The aim of this research is to find out how the creativity of Islamic religion teachers is in improving the quality of Islamic education at SMP IT Ishlahul Ummah Prabumulih. The research method uses a qualitative approach, the data is taken through observation, interviews and documentation, then reduced as well described qualitatively. Research result First, the teacher's creativity which is applied in learning Islamic religious education at SMP IT Ishlahul Ummah Prabumulih uses various ways, including in learning activities, which involve improving the teaching system, teachers are required to create a learning system in the classroom more attractive, comfortable, safe and fun. Second, supporting factors: a high student enthusiasm for learning, b school activities that pay great attention to religious issues, c supportive discipline, d programs that are directed towards educational goals, e qualified teachers a conducive school environment, g supportive extracurricular, h supporting school facilities and infrastructure including libraries, chemistry laboratories and computers. While the inhibiting factors: a student's background, b students' ability to grasp heterogeneous learning, c lack of awareness of students to be disciplined. So it can be concluded that the creativity of each teacher varies and the application of the creativity of the religious teacher is adjusted to the material, student conditions and the environment.